Asymmetric total syntheses and structure confirmation of chlorofucins and bromofucins - Kim, B; Sohn, T; Kim, D; Paton, R (Wiley, 2018)
Substrate-controlled asymmetric total syntheses and structure confirmation of (+)-(3E)- and (-)-(3Z)-chlorofucin [(E)-1 a and (Z)-1 a], and (+)-(3E)- and (-)-(3Z)-bromofucin [(E)-1 b and (Z)-1 b] were accomplished. Our syntheses feature as key steps haloetherification (either 'conventional' or 'one-pot organoselenium-mediated') of α,α'-trans-γ,δ-unsaturated oxocene alcohol 9 and our (E)- and (Z)-selective cross-metathesis (CM) protocols. More importantly, a rationale is provided for the strikingly different pathways followed by α,α'-trans-γ,δ-unsaturated oxocene alcohol 9 and its α,α'-cis isomer 9' in the presence of different electrophiles during the intramolecular electrophilic addition reactions.